Elevated tumor necrosis factor alpha and vascular endothelial growth factor in intermediate age-related macular degeneration and geographic atrophy - Rajeswaren, Vivian; Wagner, Brandie D.; Patnaik, Jennifer L.; Mandava, Naresh; Mathias, Marc T.; Manoharan, Niranjan; de Carlo Forest, Talisa E.; Gnanaraj, Ramya; Lynch, Anne M.; Palestine, Alan G.; , the University of Colorado Retina Research Group (Frontiers in Ophthalmology, 2024)
IntroductionTumor necrosis factor alpha (TNF-α) is an inflammatory cytokine implicated in pathological changes to the retinal pigment epithelium that are similar to changes in geographic atrophy (GA), an advanced form of age related macular degeneration (AMD). TNF-α also modulates expression of other cytokines including vascular endothelial growth factor (VEGF), leading to choroidal atrophy in models of AMD. The purpose of this study was to investigate systemic TNF-α and VEGF in patients with GA and intermediate AMD (iAMD) compared to controls without AMD.MethodsWe examined plasma levels of TNF-α and VEGF in patients with GA, iAMD, and controls without AMD from the University of Colorado AMD registry (2014 to 2021). Cases and controls were characterized by multimodal imaging. TNF-α and VEGF were measured via multiplex immunoassay and data were analyzed using a non-parametric rank based linear regression model fit to plasma biomarkers.ResultsThere were 97 GA, 199 iAMD patients and 139 controls. TNF-α was significantly increased in GA (Median:9.9pg/ml, IQR:7.3-11.8) compared to iAMD (Median:7.4, IQR:5.3-9.1) and in both GA and iAMD compared to controls (Median:6.4, IQR:5.3-7.8), p<0.01 for all comparisons. VEGF was significantly increased in iAMD (Median:8.9, IQR:4.8-14.3) compared to controls (Median:7.7, IQR:4.6-11.1), p<0.01. There was a significant positive correlation between TNF-α and VEGF in GA (0.46, p<0.01), and iAMD (0.20, p=0.01) with no significant interaction between TNF-α and VEGF in any group.DiscussionThese findings suggest TNF-α and VEGF may contribute to systemic inflammatory processes associated with iAMD and GA. TNF-α and VEGF may function as systemic biomarkers for disease development.